A reportagem-poema em Guilherme de Almeida: um estudo da série Cosmópolis - Santos, Michelle Moreira Braz [UNESP] (2012)
This research performs and analytical-interpretative study of the series of reports Cosmópolis, the poet Guilherme de Almeida, published in the newspaper O Estado de S. Paulo during the period from March 1929. Aware of the increasing immigration flow and urbanization, Guilherme de Almeida invites us to a narrative-poetic look at eight foreign quarters in São Paulo. This corpus also encourages us to questions about hybridity located both in transgression of the boundaries between prose and poetry and in breaking boundaries between journalism and literature. Thus, to study the series of reports Cosmópolis appealed mainly to the journalism theories focused on the issue of jourlaistic genres, as well as the works of literacy criticism and poetic analysis. In addition, we seek to fabricate an immigrant perception of analysis in this peculiar record of the current São Paulo immigration in the 20s